Muslim Diaspora dalam Isu Identitas, Gender, dan Terorisme - Damanuri, Aji (Program Pascasarjana UIN Sunan Ampel Surabaya, 2012)
The word Diaspora has been understood as the dissemination of certain group of people -notably the Jewish and Chinese- to other country or land while keeping in touch culturally with the country of their origin. This paper discusses this notion of Diaspora in the case of Muslims by relating it to the problems of identity, gender and terrorism. The paper asks whether Muslim migration to other countries is a form of shame or honor both for Muslims themselves and for the country of their destination. The three key issues that we raise will be used as both indicators and framework within which the notion of Muslim self-esteem is investigated. The underlining view that highlights the whole argument of the paper is that a great majority of Muslims in Diaspora has not been able to associate culturally with the country of destination, hence creating a tension with the local culture.